Best Answer

4xy²(3y-x)-2x²(x-3y)²=4xy²(x-3y)-2x²(x-3y)²=(x-3y)[4xy²-2x²(x-3y)²]=(x-3y)(4xy²-2x³+6x²y)=(x-3y)(-2x³+6x²y+4xy²)=-2x(x-3y)(x²-3xy-2y²)= -2x(x-3y)(x-y)(x-2y)

User Avatar

Wiki User

8y ago
This answer is:
User Avatar
More answers
User Avatar


Lvl 1
4y ago

4xy² -2x²

This answer is:
User Avatar

Add your answer:

Earn +20 pts
Q: How do you factorize 4xy²(3y-x)-2x²(x-3y)² to get -2x(x-3y)(x-y)(x-2y)?
Write your answer...
Still have questions?
magnify glass
Related questions

What is the golden rule of factorization?

Factorize others as you would have them factorize you.

What is 6ab-3b factorize?

6ab-3b factorize = 3

Factorize the number 1584 answer?

2x2x2x2x3x3x11 =) Go to ( to learn how to factorize

How do you factorize a prime number in index notation form?

Prime numbers don't factorize; they're already prime.

How do you factorize using the quadratic formula?


How do you factorize 3a-3?


How do you factorize 612?

612=22 • 32 • 17

How do you prime factorize 15?

3 times 5

How do you factorize x?

7 - x is in its simplest form.

How do you factorize 3m-mp?

It is: m(3-p)

How do you factorize 10v 12u?

2(5v + 6u)

Factorize these expression 10-25w?

the answer is 2-5w